Development and validation of assay methods for the quantitative determination of drugs and their metabolites in biological specimens (piroxicam and nabumetone) - De Jager, Andrew David (University of the Free State, 2001)
The development and validation of bioanalytical assay methods suitable for the quantitation of drugs in biological matrices is discussed, as well as general principles applicable to this particular aspect of drug development. Relevant literature is consulted, with a view to exemplifying what constitutes good assay method development strategy, as well as to reflect current international policy in this field, with particular reference to bioequivalence studies. Comparisons are made between international practices and those in place at FARMOVSPAREXEL Bioanalytical Services Division®. Attention is given inter alia to detector selection, chromatographic optimisation, extraction procedures and method validation, with reference to new assay methods for two drugs in particular that have been developed and validated according internationally acceptable standards. In the first instance, a highperformance liquid chromatographic method with ultraviolet detection was developed for the determination of 6-methoxy-2-naphthylacetic acid (6-MNA, the active metabolite of nabumetone ). The sample preparation involved a simple but effective protein precipitation procedure. Reversed-phase liquid chromatography was optimised, and full resolution between the analyte and endogenous matrix peaks achieved in a chromatographic runtime of five minutes. The assay method was validated over a range of plasma concentrations between 0.070 and 145 µg/ml. 1242 Plasma samples generated during a comparative bioequivalence study were then assayed and the performance of the assay method shown to be well within accepted international norms. The coefficient of variation for quality control standards over the range of 0.18 to 39 µg/ml processed during the assaying of the study samples, varied between 3.6 and 8.1 %. In the second instance, a novel method for the determination of piroxicam in four biological matrices (sub-cutaneous tissue (SCT), synovial fluid (SF), synovial capsule (SC) and plasma) was developed. A double back-extraction procedure was followed by reversed-phase liquid chromatography and electrochemical detection (ECD). Extracts from all four biological matrices were injected onto a single HPLC system. Ratios between plasma and the three remaining matrices were used to characterise transdermal absorption of two topical preparations of piroxicam when applied to the knee. Low systemic levels associated with topical formulations necessitated the development and validation of a highly sensitive assay method. Plasma was used as a surrogate matrix for all the processed tissue samples and the assay method was validated over a range of plasma concentrations between 1.24 and 600 ng/ml. 168 Samples generated during a multi-centre study involving knee replacement surgery, were assayed and the performance of the assay method shown to be well within accepted international norms. The coefficient of variation for quality control standards over the range of 1.74 to 300 ng/ml processed during the assaying of the study samples, varied between 7.7 and 13.5 % which can be considered excellent in the light of the complexity of the sample preparation process. Analytical data generated during the above-mentioned two research projects are discussed, with novelties and improvements to existing assay methods being elucidated. Both assay methods were presented and accepted for publication in peer reviewed scientific journals. Both full-length publications are included in an appendix in this dissertation, together with the correspondence entered into with journal editors and referees. Furthermore, a section containing copies of the slides used to present the latter HPLC assay method as an oral presentation at the 1998 Annual Congress of the South African Pharmacological Society, is included.

Die ontwikkeling en validering van bioanalitiese metodes wat vir die kwantifisering van geneesmiddels in biologiese monsters toepaslik is, asook algemene beginsels wat van toepassing is op hierdie aspek van geneesmiddelontwikkeling, word bespreek. Relevante literatuur is geraadpleeg met die doelom voorbeelde van sinvolle strategieë vir die ontwikkeling van bioanalitiese metodes uit te lig asook om huidige internasionale praktyke, veral ten opsigte van bioekwivalensiestudies, te reflekteer. In die verhandeling word vergelykings tussen bogenoemde praktyke en dié by FARMOVS-P AREXEL Bioanalytical Services Division® getref. Onder andere word aandag aan die keuse van die detektor, chromatografiese optimisering, monster voorbereiding en validering van twee nuwe analitiese metodes gewy wat albei ontwikkel en valideer is volgens internasionaal aanvaarde standaarde. Eerstens is 'n hoë-verrigting vloeistofchromatogra-fiese metode met ultravioletdeteksie vir die bepaling van 6-metoksie-2-naftiel asynsuur (6-MNA, die aktiewe metaboliet van nabumetoon) ontwikkel. Die monstervoorbereiding behels 'n eenvoudige maar baie effektiewe proteïen presipitasie van plasmamonsters gevolg deur omgekeerde vloeistofchromatografie. Die sisteem is geoptimiseer en skeiding tussen die analiet en endogene plasmakomponente geskied binne die bestek van 'n vyf minute chromatografielopie. Die metode is oor 'n bereik van 0.070 en 145 µg/rnl plasmakonsentrasies gevalideer. 1242 Plasmamonsters wat gedurende ,n vergelykende biobeskibaarheidsstudie verkry is, is dan geanaliseer en die verrigting van die analitiese metode was gemaklik binne aanvaarde internasionale norme. Die variasiekoëffisiënt van die kwaliteitskontroles wat in die studie saam met die studiemonsters geproseseer is, en wat oor 'n konsentrasiebereik van 0.070 en 145 µg/ml gestrek het, het gevariëer tussen 3.6 en 8.1 %. Die tweede navorsingsstuk behels die bepaling van piroksikam in vier verskillende biologiese matrikse (subkutane weefsel, sinoviale kapsel, sinoviale vog en plasma). 'n Dubbele terug-ekstraksie, gevolg deur omgekeerde fase vloeisstof-chromatografie en elektrochemiese deteksie was angewend om piroksikam te kwantifiseer. Ekstrakte uit elk van die vier verskillende matrikse is op 'n enkele HPLC sisteem ingespuit. Verhoudings tussen plasmakonsentrasie en die konsentrasie van piroksikam in die drie oorblywende matrikse is bereken om die transdermale absorpsie van piroksikam uit twee topikaal, op die knie aangewende preparate, te karakteriseer. Aangesien die aanwending van topikale piroksikam gelpreparate maar baie lae sistemiese piroksikarnkonsentrasies lewer, was dit nodig om 'n baie sensitiewe analitiese te ontwikkel. Plasma was gebruik as 'n surrogaatmatriks vir die geproseseerde weefselmonsters en die analitiese metode was gevalideer oor 'n plasmakonsentrasie-bereik van 1.24 tot 600 ng/ml. 168 Monsters wat ontvang is uit 'n multisentriese studie waarby knievervangssjirurgie betrokke was, is geanaliseer en die verrigting van die bepalingsmetode was gemaklik binne die internasionaal aanvaarde norme. Die variasiekoëffisiënt van die kwaliteitskontroles wat in die studie saam met die studiemonsters geproseseer is, en wat oor 'n konsentrasiebereik van 1.70 en 300 ng/ml gestrek het, het gevariëer tussen 7.7 en 13.5 % wat as uitstekend gereken kan word in die lig van die kompleksiteit van die monstervoorbereiding. Analitiese gegewens wat gedurende die twee bogenoemde navorsingsprojekte versamel is , word bespreek, en veral verbeteringe en nuwighede ten opsigte van bestaande bepalingsmetodes word uitgelig. Beide bepalingsmetodes is vir publikasie in aanstaande wetenskaplike joernale aanvaar en beide vollengte publikasies verskyn as bylae tot hierdie verhandeling tesame met alle korrespondensie wat met die j oumaal redakteur en referente aangegaan is. Verder is 'n bylaag ingesluit wat die skyfies bevat wat tydens die 1998 Jaarlikse Kongres van die Suid Afrikaanse Farmakologievereniging gebruik is in 'n mondelinge voordrag oor die piroksikam bepalingsmetode.
Dissertation (M.Med.Sc. (Pharmacology))--University of the Free State, 2001
Keywords: Method development; Validation; Drug development; Bioequivalence; High-performance liquid chromatography; Plasma; Sub-cutaneous tissue synovial capsule; Synovial fluid; Biological assay; Drugs -- Analysis